2001
DOI: 10.1515/cclm.2001.054
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of Apoprotein E (APOE), Methylenetetrahydrofolate Reductase (MTHFR) and Paraoxonase (PON1) Genes in Patients with Cerebrovascular Disease

Abstract: Although controversial, data on the genetic polymorphism of apoprotein E (APOE), methylenetetrahydrofolate (MTHFR) and paraoxonase (PON1) genes implicate their role in the development of cerebrovascular disease. The aim of this study was to assess the association of polymorphism of APOE, MTHFR and PON1 genes in 56 stroke and 36 carotid stenosis patients, and in 124 control subjects by PCR-restriction fragment length polymorphism analysis. In the stroke group a significantly different MTHFR genotype distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 29 publications
1
32
1
2
Order By: Relevance
“…11,12 In a small study from Croatia that examined 56 stroke cases and 124 controls, there was no significant difference in the frequency of the Arg192 allele between the 2 groups. 10 There was no evidence of heterogeneity of odds ratios across the 4 studies ( 2 3df ϭ4.76, Pϭ0. 19), however, and the combined odds ratio for the Arg192 allele versus Gln192 allele was 1.64 (95% CI, 1.39 to 1.94).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…11,12 In a small study from Croatia that examined 56 stroke cases and 124 controls, there was no significant difference in the frequency of the Arg192 allele between the 2 groups. 10 There was no evidence of heterogeneity of odds ratios across the 4 studies ( 2 3df ϭ4.76, Pϭ0. 19), however, and the combined odds ratio for the Arg192 allele versus Gln192 allele was 1.64 (95% CI, 1.39 to 1.94).…”
Section: Resultsmentioning
confidence: 94%
“…However, in a fourth study, the difference in frequency of the high-risk Arg192 allele between stroke cases and controls was not significant. 10 This lack of association could be the result of differences in diagnostic criteria for stroke or population differences.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analyses suggest that the PON1 Q192R and PON1 M55L (and in one study, PON1 -108C/T ) genotypes do not predict cardiovascular disease (CVD) (26)(27)(28). Interestingly, a study of severity of CVD did show a PON1 Q192R effect (29), and the studies for prediction of stroke or CAAD (22,(30)(31)(32)(33)(34) have been more consistently positive for a PON1 locus effect, although negatives occur (35) and the studies tend to be small. Of note, the polymorphisms previously studied represent only a small fraction of PON1 genetic variation: reported studies have examined only a handful of the more than 150 known PON1 region polymorphisms.…”
mentioning
confidence: 99%
“…In the next decade, five metaanalyses [17-19, 21,23] confirmed that ε4 allele carriers have a higher risk of IS compared with pooled ε2 and ε3 allele carriers in European populations, persons of non-European descent, Asians, Han Chinese and persons with early-onset IS. Performing large-scale meta-analysis (10674 cases/33430 controls) consisted of four meta-analysis [19,[21][22][23] and 9 case-control studies [33,35,36,54,59,65,66,84,88], Hamzi et al [24] calculated OR for the apo4 allele to be 0.95 (95%CI 0.77-1.14, P=0.002).…”
Section: Candidate-gene Association Studies Of Ischemic Strokementioning
confidence: 99%
“…According the literature data there are three metaanalysis [18,174,175] and 26 casecontrol studies [28,30,34,35, explored the association of PON1 polymorphisms and IS risk. A positive association of Gln192Arg PON1 polymorphism and IS was described in the metaanalyses and in five case-control studies [177,178,184,185,188], but this association was negative in all other reports.…”
Section: Paraoxonase(pon)mentioning
confidence: 99%